The symmetry and coupling properties of solutions in general anisotropic multilayer waveguides - Hernando Quintanilla, F; Lowe, M J S; Craster, R V (The Journal of the Acoustical Society of America, 2017)
Multilayered plate and shell structures play an important role in many engineering settings where, for instance, coated pipes are commonplace such as in the petrochemical, aerospace, and power generation industries. There are numerous demands, and indeed requirements, on nondestructive evaluation (NDE) to detect defects or to measure material properties using guided waves; to choose the most suitable inspection approach, it is essential to know the properties of the guided wave solutions for any given multilayered system and this requires dispersion curves computed reliably, robustly, and accurately. Here, the circumstances are elucidated, and possible layer combinations, under which guided wave solutions, in multilayered systems composed of generally anisotropic layers in flat and cylindrical geometries, have specific properties of coupling and parity; the partial wave decomposition of the wave field is utilised to unravel the behaviour. A classification into five families is introduced and the authors claim that this is the fundamental way to approach generally anisotropic waveguides. This coupling and parity provides information to be used in the design of more efficient and robust dispersion curve tracing algorithms. A critical benefit is that the analysis enables the separation of solutions into categories for which dispersion curves do not cross; this allows the curves to be calculated simply and without ambiguity.